Risk of Anthropogenic hazards in Kashmir and their management - Sharma, Geetu; Hussain, Sarfaraz (Innovative Research Thoughts, 2017)
Jammu and Kashmir is one of the most politically difficult areas in NW Himalaya, and possibly also one of the most unlucky parts of the planet Earth where political and natural catastrophes have severely destroyed the progressive development of the region. The geological history of this area indicates that it was created when Indian tectonic plate collided with the Eurasian plate, and this also produced several intermontane basins, which house most of the people of the region. As the tectonics is still actively changing the topography, geology, geomorphology, and climate of the region, the occurrence of earthquakes and floods in the area is possibly unavoidable. Our understanding of the causes of earthquakes informs us that it is time to place more focus on preparation rather than on the forecast, which is partially true of flood risks as well.